Valuing Critical Inquiry Skills in Museum Literacy. Issue 3 (1st November 2016) - Gilbert, Lisa
Abstract : As content acquisition is often conceived of as the primary goal of a museum visit, advice for social studies teachers on making the most of field trips primarily focuses on ways to increase the information absorbed by students. Yet, research in museum studies provides ample evidence for questioning this underlying assumption. This article presents a former museum professional's view on the educational potential of museum spaces, suggesting critical inquiry is a key skill of museum literacy. First, a historical view of museums shows how society has inscribed the institutions and their content with unwarranted authority. Secondly, an insider's view of the exhibit creation process raises questions about the nature of the content we are often eager for students to consume. Third, an overview of research in museum studies offers an alternative understanding of the nature of learning in museum spaces. Finally, practical suggestions are given for valuing critical inquiry as part of museum literacy. For social studies educators interested in empowering their students to become reflective citizens, a key component of museum literacy will be critical engagement with not only the narratives on display, but also the institutions that house them.